SUN-LB6 Characterization of PCOS Among Flo App Users Around the World - Galic, Isabel (J Endocr Soc, 2020)
Polycystic ovary syndrome (PCOS) is a common gynecological endocrine disorder associated with menstrual irregularity and androgen excess. The worldwide prevalence of PCOS among women of reproductive age ranges from 5-20%. Mobile menstrual cycle apps, such as Flo, provide an opportunity to gather data on the characteristics of PCOS in a globally representative and medically unbiased population. The objective of this study was to report PCOS symptomatology relative to country in order to better characterize PCOS and its differing phenotypes among users around the world. A questionnaire on PCOS related symptoms and previous PCOS diagnosis was available to Flo users during one month (2019). The geographical location of the user was estimated based on the IP address. Study inclusion criteria included women aged 18-44 years seeking to track their cycle or to conceive, who were not pregnant, on active contraception, or in stabilization mode after pregnancy and had Flo app running in English. All users in the study had agreed to the use of their de-identified and aggregated data for research purposes.The highest number of Flo app users who completed the PCOS questionnaire were coming from the following top 5 countries: United States (US) (n=240,732), United Kingdom (UK) (n=67,696), India (n=40,171), the Philippines (n=35,097), and Australia (n=28,946). The percentage of self-reported PCOS in these countries was 14.4% with higher percentages in India, the Philippines, and Australia (22.6%, 20.0%, 15.9, respectively) and lower in the US and UK (12.2% and 13.71%, respectively). In the US, UK, and Australia, the most common self-reported symptoms of PCOS positive women were bloating, hirsutism, and irregular cycles. In India and the Philippines, the most common symptoms of women with PCOS were bloating, baldness, and irregular cycles. Hirsutism, high glucose and high levels of both cholesterol and glucose are the three top symptoms increasing the probability of PCOS in all studied countries. The percentage of self-reported PCOS increases 3.04 times among users that reported hirsutism compared to all users that positively responded to the PCOS self-assessment question. Probability of PCOS among users that report hirsutism increases 3.85 times for Australia and 4.24 times for India. Australia and India had higher percentages of self-reported PCOS among those who reported experiencing nearly all PCOS related symptoms. Using Flo’s software, we are able to determine that geographic location has an effect on the phenotypic presentation of PCOS. Understanding the distribution of PCOS symptomology around the world will help to better characterize PCOS and improve diagnosis and treatment on both an individual and global scale.